The Role of Mahatma Gandhi in the Development of the National Movement in India 1919-1930 - Khader, Sabla Talal Yassin Abdel (International Journal of Psychosocial Rehabilitation, 2020)
The Indian political scene witnessed many developments during the period 1919-1930. The Gandhi leadership was born to the political theater, as Gandhi star emerged after his arrival from South Africa to India in 1915, and Gandhi was the first work he undertook after two years spent in religious work and training people How to use (Aalsatia Graha) nonviolence. In 1919 a law was passed (rolls) by the British authorities, who promised him how much as Afa of the Indians to serve in World War I, while several Indian law a Unjust A against their aspirations and their future. In the same year, the (Gallino Bagh) massacre occurred, which was considered one of the ugliest massacres in the history of British rule in India. During this the duration of Gandhi adopted new methods approved by the party, the National Conference of the Indian of these movements of non - violence and non - cooperation civil disobedience and marches peaceful protest led by Gandhi was the most important of the march of salt in came this research to answer the way that was the Gandhian leadership of the Indian masses during the duration 1919 – 1930.